METHODOLOGY FOR THE DEVELOPMENT OF DIGITAL COMPETENCE OF RESEARCH AND PEDAGOGICAL STAFF USING THE INTERNATIONAL UKRAINIAN NATIONAL H-INDEX RANKING - Novytska, Т. Л. (Journal of Information Technologies in Education (ITE), 2025)
The article is devoted to the substantiation and development of a methodology for the development of digital competence of scientific and scientific-pedagogical staff using the international non-profit rating Ukrainian National H-index Ranking (Ukrainian NHR). The functionality, main indicators, key aspects, shortcomings and uniqueness of the Ukrainian NHR ranking are analyzed. The representation of a domestic scientific institution in the Ukrainian NHR ranking on the example of the Institute for Digitalisation of Education of NAES of Ukraine is considered In order to implement the development of digital competence of scientific and scientific-pedagogical staff using the international Ukrainian NHR ranking, a special course «Development of digital competence of scientific and scientific-pedagogical staff using the international Ukrainian National H-index Ranking» has been developed, which consists of two modules: 1. Theoretical foundations of digital competence and methods of its development and 2. Using the international rating Ukrainian NHR. The methodology for developing the digital competence of research and pedagogical staff is based on the rating and includes: the purpose of training, target audience, main tasks, forms, methods, learning tools, and the expected result. After completing the course, students will be able not only to improve their digital competence but also to contribute to the development of the scientific sphere in Ukraine using the tools and techniques they have mastered during their studies. The developed methodology demonstrates that the integration of the Ukrainian NHR system into the educational process is a promising way to improve the efficiency of education and science. It allows not only to develop skills but also to stimulate scientific productivity, and helps to increase the digital competence of researchers, preparing them for new challenges in modern science.